Management of Breast Cancer During Pregnancy - Rincon, Victor Andres Diaz; Cuello, Dalila Rosa Fernández; Lora, Juan Felipe Villegas; Ayala, Gabriela Carolina Alvear; García, Juan Sebastián Rivas; Zabaleta, Karen Medina; Estrada, Daniela Gallón; Adames, Gabriel Alejandro Córdoba; Quiroga, July Paola Ramirez (Jour Med Resh and Health Sci, 2022)
Background: Breast cancer is the most common type of cancer in women throughout the world during reproductive age, it is the most frequent neoplasm in women, its etiology being unknown and probably related to multiple factors. It usually presents as a mass, being essential to perform a breast imaging test and biopsy suspicious lesions. Methodology: A narrative review was carried out through various databases from 2012 to 2021; the search and selection of articles was carried out in journals indexed in English and Spanish. Keywords were used: approach, breast cancer, pregnancy. Results: to guarantee quality care, the main finding to highlight is a painless nodule in the breasts, the treatments are the same applied to non-pregnant women, but with limitations to maintain fetal well-being, and the main interventions are prevention and detection early breast cancer in pregnant women, and apply individualized care plans prepared as the case may be. Conclusion: when detecting a palpable mass or abnormal lump in the breasts of a pregnant patient, it is necessary to delve into the etiology of this abnormality, in order to determine with solid criteria the approach regarding the treatment of pregnant patients, this should be safe and must be approached in a multidisciplinary way.